Stabilisation through digital technology: How CAD programmes contribute to spatial order in planning - Kuppler, Anne; Alpermann, Hendrikje (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Planning is generally recognised as the practice of spatial organisation. Planning instruments, such as land-use plans and zoning plans, are used to structure development, to reduce building densities and to densify. While planning instruments themselves and their interpretation, practical use and implementation have been widely studied, in contrast technical implementation and its active role in planning processes have remained mostly unexplored. This paper addresses this research gap by considering the ways in which common techniques – primarily graphical CAD programmes – operate in planning processes. The basic assumption here is that CAD programmes not only make planning possible, but also play a significant role in shaping it, since digital technology is used to inscribe and stabilise spatial organisation in plans. Prominent concepts from Science and Technology Studies are used to demonstrate how CAD programmes give urban complexity a new material form – that of the plan. They contribute significantly to a core area of planning and thus to the specific ordering of our built environment.